The Role of Guidance and Counseling Teachers in Fostering Students' Character Development During The Period of Independent Curricula is Crucial - Siregar, Zahwa Aulia; Susanti, Putri Zeni; Cahyani3, Muthia; Febriani, Vina; Oktarini, Ira; Sabarrudin, Sabarrudin (Educational Guidance and Counseling Development Journal, 2024)
The self-directed curriculum places a high value on character education, which is crucial for cultivating people of extraordinary caliber in a community that governs itself. The independent curriculum places a high importance on developing students' character, which includes fostering moral ideals, ethics, honesty, leadership, and cooperation. The main goal of this character education program is to cultivate in children the qualities of responsibility, empathy, and moral integrity, thus promoting the establishment of a fair and unbiased society. Character education is crucial for implementing the autonomous curriculum and fostering a generation that possesses both academic intelligence and robust moral beliefs and positive dispositions. Character education is essential for influencing students' views and enhancing their personal development. The independent curriculum aims to strengthen the character of the Pancasila student profile by prioritizing the principles and values of Pancasila. The Pancasila Student Profile has the following components: belief in a supreme being, ethical uprightness, acknowledgment of global diversity, ability to work collaboratively, self-reliance, and analytical and creative thinking. The role of guidance and counseling teachers in promoting students' character development during the period of independent curriculum is vital.